Scoping the Possible Economic Implications of Brexit on Ireland - Barrett, Alan; Bergin, Adele; FitzGerald, John; Lambert, Derek; McCoy, Daire; Morgenroth, Edgar; Siedschlag, Iulia; Studnicka, Zuzanna (ESRI, 2015)
With the UK government committed to holding a referendum on membership of the EU, it is important that we understand the possible implications for Ireland. In this study, ESRI researchers explore the economic links between Ireland and the UK and scope out the possible economic consequences of Brexit for Ireland.